Relationship Between Socio-Demographic Correlates and Human Development Index with Physical Activity and Sedentary Time in a Cross-Sectional Multicenter Study - De Moraes-Ferrari, G (BioMed Central Ltd, 2022)
Background: Socio-demographic correlates and human development index (HDI) are associated with self-reported physical activity, but only a few studies have focused on device-measured physical activity and sedentary time in Latin America. We examined the relationship between socio-demographic correlates and HDI with physical activity and sedentary time in a cross-sectional study. Methods: We based our analyses on 2522 (53.1% women; 18–65 years [mean age 38.3 years]) adults drawn from the eight Latin America countries. Physical activity (light, moderate, vigorous, and moderate-to-vigorous intensity and steps) and sedentary time were assessed using Actigraph GT3X + accelerometers. Sex, age, and race/ethnicity were self-reported. The HDI country information was obtained from the United Nations Development Program. Results: For the age, ethnicity, vigorous physical activity and steps/day, there were significant differences between high and very high HDI countries. Women and younger age presented lower sedentary time than men and older. In moderate-to-vigorous physical activity, we found lower duration in women (-13.4 min/week), younger age (-0.1 min/week), and white/caucasian (-2.7 min/week) than men, older ages and mixed ethnicity. Women (-1266.5 steps/week) and very high HDI (-847.3 steps/week) presented lower steps than men and high HDI. Black (2853.9 steps/week), other (1785.4 steps/week), and white/caucasian ethnicity (660.6 steps/week) showed higher steps than mixed ethnicity. Conclusions: Different socio-demographic correlates are associated with physical activity intensity; however, HDI is associated with vigorous physical activity and steps in the Latin American region, which can in turn guide policies to promote physical activity in the region. Trial registration: ClinicalTrials.GovNCT02226627. Retrospectively registered on August 27, 2014. © 2022, The Author(s).